Thinking ethics differently (challenges and opportunities for engineers education) - Pasca, Carmen Mariana (2021)
Ethics has many definitions, each depending on its domain. In the ancient times, ethics was based on the principles of good action and the search for the common good.  Generally, Ethics is understood as a system of moral principles which affect our ways of living. Ethics are related with what is good for society and individuals and is described as moral philosophy. Ethics only makes sense if we put them in the context of human action understood as responsible, creative and communicative. Applied Ethics and Codes of conducts have appeared in the contemporary period. One of the key issues in the engineering education ethics program is the problem of margins/limits of autonomy that will enable future engineers to act ethically in accordance with universal ethical principles and the existing codes of ethics. Computer ethics adds the intellectual property rights, and also the use of personal data. The paper shows a general review of ethics, its history, its evolution, with an emphasis on engineering education. It also mentions the big data issue in ethics.